1998
DOI: 10.1080/08873267.1998.9976975
|View full text |Cite
|
Sign up to set email alerts
|

The connectedness model and optimal development: Is ecopsychology the answer to emotional well-being?

Abstract: To help mitigate the impact of multi-environmental degradation, I have constructed, implemented, and researched a program for emotionally at-risk children using nature in a therapeutic format. Based on the Piers-Harris self-concept scale and person drawings, the children demonstrated a post-program increase in self-esteem (p < .001), happiness, educational status, and emotional development (p < .001). They also demonstrated enhanced perceptual skills, self-efficacy, empathy and a significant reduction in aggre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 48 publications
(66 reference statements)
2
35
0
1
Order By: Relevance
“…From this perspective, the natural world is not separate from humanity; but it is at the 4 very core of humanity, even if we live in a material and cultural world which may attempt to deny recognition of this fact. Feelings of connection, unity or being a part of the natural world, according to this perspective, are a causal step to psychological health (Feral, 1998).Thus feelings of connection to nature would be expected to correlate with reduced anxiety (Besthorn & Canada, 2002;Mayer & Frantz, 2004;White, 2011). As anxiety is a mental health problem with increasing prevalence, creating further understanding of the anxiety-nature relationship would be beneficial.…”
Section: Introductionmentioning
confidence: 99%
“…From this perspective, the natural world is not separate from humanity; but it is at the 4 very core of humanity, even if we live in a material and cultural world which may attempt to deny recognition of this fact. Feelings of connection, unity or being a part of the natural world, according to this perspective, are a causal step to psychological health (Feral, 1998).Thus feelings of connection to nature would be expected to correlate with reduced anxiety (Besthorn & Canada, 2002;Mayer & Frantz, 2004;White, 2011). As anxiety is a mental health problem with increasing prevalence, creating further understanding of the anxiety-nature relationship would be beneficial.…”
Section: Introductionmentioning
confidence: 99%
“…Although the positive mental health characteristics of connecting with nature have often been associated with spirituality (Barlett, 2005;Feral, 1998;Glassman, 1995;Kaplan & Talbot, 1983;Merkl, 1995), studies of restorative environments have shown that simply spending time in natural settings can also lead to reduced stress or a quicker recovery from stress (Heerwagen, 1990;Parsons et al, 1998;Ulrich, 1993;Ulrich et al, 1991;Wells & Evans, 2003). Mayer and Frantz (2004) found evidence that spending time in natural settings is correlated with a sensed connection with the natural world.…”
mentioning
confidence: 99%
“…Feral (1998Feral ( & 1999 uses ecopsychology for children therapy; Rhodes (2008) uses ecopsychology in modern day human therapy through ecospiritual and ecofeminism; Wood (2010) uses ecopsychology with ecospiritual therapy; Burn (2012) & Tudor (2013 use ecopsychology for ecotherapy that leads to self-therapy; Hafford (2014) uses ecopsychology for adventure therapy; And Black (2015) uses ecopsychology for natural therapy of healing.…”
Section: The Second Stage: An Understanding Of the Flow/field O Arablmentioning
confidence: 99%